GRATITUDE AS POSITIVE CHARACTER STRENGTH: THE INVESTIGATION OF IT’S RELATIONSHIP WITH MENTAL WELL-BEING AND SOME DEMOGRAPHIC VARIABLES - Tuğba SARI (Fırat University, 2019)
The purpose of this study is to investigate the relationship between gratitude and mental well-being, and some demographic variables (gender, socio-economic level, grade point average, perceived religiosity level). Research data were collected from 694 university students through online questionnaires in the survey. 490 of these participants (70.6%) were female and 204 (29.4%) were male and the average age was 21.40. The Gratitude Scale was used to measure gratitude and the Warwick-Edinburgh Mental Well-Being Scale was used to measure mental well-being. Kruskal-Wallis Test was used to determine whether there was a statistically significant difference between the scores. The Mann Whitney U Test was used to determine which groups differed. According to the results of the analysis, it was found that the mental well-being level of the group with a high level of gratitude was higher than the middle and low level of gratitude and at the same time the mental well-being level of the group with a mean level of gratitude was higher than the group with low. Another research finding is that the level of gratitude differs according to perceived level of religiousness. It is found that as the perceived level of religiousness increases and the level of gratitude also increases. Besides, it was determined that the level of gratitude of the groups with different grade point averages differed. According to this, the level of gratitude of i